Response Surface Method Analysis of Gas-Sensitive Properties: Investigating the Influence of External Environment on the Performance of Semiconductor Gas Sensors - Li, Yudong; Yuan, Zhenyu; Ji, Hanyang; Meng, Fanli; Wang, Hao (IEEE transactions on industrial electronics (1982), 2024)
Gas sensors based on semiconductor metal oxide (SMO) demonstrated commendable efficiency in gas detection, but susceptibility to environmental fluctuations remains a noteworthy concern. Given the inherent intricacies of the gas detection process, it is imperative to undertake a comprehensive investigation into the multifaceted implications of environmental variations on sensor performance. In this research, we selected a laboratory-fabricated porous ZnO nanosphere gas sensor as the subject of study, which showcased a remarkable response (148) to 100 ppm ethanol, a response/recovery times of 29.5/141 s, along with a detection limit of 50 ppb.To elucidate the influence of environmental changes on sensor performance, we harnessed the response surface method (RSM) as an analysis tool. Furthermore, we expanded the utility of RSM to forecast the gas-sensing response, response time, and recovery time for both laboratory-fabricated and commercial sensors. The average errors associated with the laboratory sensors were determined to be 6.00%, 5.84%, and 6.75%, respectively, while those of the commercial sensors were 3.62%, 4.96%, and 5.09%. These disparities comfortably fall within established acceptable limits, underscoring RSM's practicality and precision in predicting the gas properties of SMO-based gas sensors.